Microbiological Analysis On Bone Flour Patin Fish (Pangasius Hypophthalmus Sp.) Biscuit Is Rich In Calcium For Children - Dewi Sartika Siagian; Wahyu Margi Sidoretno; Sri Kartini (Universitas 'Aisyiyah Yogyakarta, 2021)
Ikan Patin bones are a by-product of the fish processing industry which contains the most calcium from the fish body because the main elements of fish bones are calcium, phosphorus and carbonate. Biscuits are snack that have a water quality standard of less than 5% so that they have a crunchy texture. The purpose of this study was to see microbial contamination in biscuits using the ALT (Total Plate Number) method. The results of microbial contamination meet the specified requirements and are included in the category of safe and normal standards according to SNI 2973:2011.